2018
DOI: 10.1021/acs.jpca.8b07770
|View full text |Cite
|
Sign up to set email alerts
|

Role of Photoisomerization on the Photodetachment of the Photoactive Yellow Protein Chromophore

Abstract: The photocycle of photoactive yellow protein (PYP) is initiated by a photoinduced trans-cis isomerisation around a C=C bond in the chromophore that lies at the heart of the protein; however, in addition to the desired photochemical pathway, the chromophore can undergo competing electronic relaxation processes. Here, we combine gas-phase anion photoelectron spectroscopy and quantum chemistry calculations to investigate how locking the C=C bond in the chromophore controls the competition between these electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…The more straightforward approaches include DFT (TD-DFT) [54] and ADC(2) [55,56] methods. We have found that the simpler TD-DFT method tends to yield VEEs that are consistently around 0.5 eV higher than those determined using higher level methods [23,25,28,29,34,35], but that the ADC(2) method compares favourably with high-level calculations, for example, with SA-CASSCF(14,12)-PT2/cc-pVDZ calculations [57] for a series of PYP chromophore anions (Table 2) [29], and XMCQDPT2/aug-cc-pVTZ level calculations [31] for the GFP chromophore anion [33]. However, due to the number of diffuse functions required in the basis set to obtain an accurate VEE, a huge number of continuum states are calculated.…”
Section: Computational Chemistry Considerationsmentioning
confidence: 71%
See 3 more Smart Citations
“…The more straightforward approaches include DFT (TD-DFT) [54] and ADC(2) [55,56] methods. We have found that the simpler TD-DFT method tends to yield VEEs that are consistently around 0.5 eV higher than those determined using higher level methods [23,25,28,29,34,35], but that the ADC(2) method compares favourably with high-level calculations, for example, with SA-CASSCF(14,12)-PT2/cc-pVDZ calculations [57] for a series of PYP chromophore anions (Table 2) [29], and XMCQDPT2/aug-cc-pVTZ level calculations [31] for the GFP chromophore anion [33]. However, due to the number of diffuse functions required in the basis set to obtain an accurate VEE, a huge number of continuum states are calculated.…”
Section: Computational Chemistry Considerationsmentioning
confidence: 71%
“…The resulting small droplets then evaporate further, eventually leading to the production of isolated gas-phase ions. ESI has been combined very successfully with photoelectron spectroscopy for studying the electronic structure of a wide range of deprotonated biomolecules, including protein chromophores [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. There are several techniques for measuring photoelectron spectra, the most popular of which are based on time-of-flight (TOF) or velocity map imaging (VMI) methods.…”
Section: Experimental Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadening of photoelectron spectra following photoexcitation of resonances in the continuum has been observed in similar sized molecular anions by many other groups 14,30,31 including our own. 11,[32][33][34][35][36][37][38][39][40][41][42] This resonance in PhO − has been observed before 12,14 and assigned to indirect detachment from the S 1 (ππ * ) state of PhO − . The S 0 -S 1 (ππ * ) transition corresponds to promotion of an electron from the HOMO shown in Table 1 to the first antibonding orbital on the phenyl ring system (the LUMO of PhO − ) and therefore has shape resonance character with respect to the D 0 continuum.…”
Section: Photoelectron Spectramentioning
confidence: 86%